Selective Immigration, Occupational Licensing, and Labour Market Outcomes of Foreign-Trained Migrants - Massimiliano Tani (Institute of Labor Economics (IZA), 2018)
This paper studies occupational licensing as a possible cause of poor labour market outcomes among economic migrants. The analysis uses panel data from Australia, which implements one of the world's largest selective immigration programmes, and applies both cross-sectional and panel estimators. Licensing emerges as acting as an additional selection hurdle, mostly improving wages and reducing over-education and occupational downgrade of those working in licensed jobs. However, not every migrant continues working in a licensed occupation after settlement. In this case there is substantial skill wastage. These results do not change over time, after employers observe migrants' productivity and migrants familiarise with the workings of the labour market, supporting the case for tighter coordination between employment and immigration policies to address the under-use of migrants' human capital.
Keywords: J8; J24; J61; 330; skilled immigration; over-education; occupational downgrade; immigration policy; occupational licensing